ASEAN Labor Market Integration and Its Social Effects for Unskilled Labor Migration - Susilo, Ignatia Bintang Filia Dei; Subchanifa, Dian Pujiatma Vera (Jurnal Economia, 2016)
Abstract: ASEAN Labor Market Integration and Its Social Effects for Unskilled Labor Migration. Member states of ASEAN mainly needed two criteria of foreign labor: highly skilled professionals or its counterpart, unskilled workers. High-skilled professionals are provided with some rights and benefits. Unskilled migrants are equipped with very limited rights and hardly subject to integration approaches. This paper will discuss the social effect of integration, notably the unskilled labor, by linking migration and remittance in ASEAN, labor based on sectored pattern, and immigration governance. Countries need to improve working conditions and wages, provide professional training and improve education for every level of workers. There are some social effects but can be managed if the governments committed to their policy.Keywords: economic integration, remittance, migrant worker, unskilled laborAbstrak: Integrasi Pasar Tenaga Kerja ASEAN dan Dampak Sosial Terhadap Migrasi Tenaga Kerja Tidak Terampil. Sebagian besar negara–negara anggota ASEAN membutuhkan tenaga kerja profesional dan tenaga kerja yang tidak terampil. Tenaga kerja profesional memiliki hak–hak khusus, fasilitas, dan berbagai keuntungan, sedangkan tenaga kerja tidak terampil hanya memiliki sedikit hak dan lebih jarang menjadi topik utama kerjasama integrasi antar negara. Artikel ini akan membahas dampak sosial integrasi, terutama bagi tenaga kerja tidak terampil, dengan mengaitkan hubungan antara migrasi dan remittance di ASEAN, sektor tenaga kerja, dan pengelolaan imigrasi yang dilakukan pemerintah. Sebagian besar negara anggota ASEAN harus meningkatkan standar kinerja dan gaji, menyediakan pelatihan, dan meningkatkan tingkat pendidikan. Terdapat beberapa dampak sosial yang muncul. Namun, beberapa dampak tersebut akan dapat ditangani apabila pemerintah memiliki komitmen dalam menerapkan kebijakannya.Kata kunci: integrasi ekonomi, remittance, pekerja migran, tenaga kerja tidak terampil